HRM Practices Across Different Cultures: An Evidence-Cased Study In France And Venezuela - Binta Zahratul Jannah; Qolbiah Safar; Shafna Maylafesya Koesnanto; Zaidan Falah Ramadhan; Muhammad Abdul Aziz; Peter Louis Calvin Lima; Sarah Aisyah (Lavish Opulent Education, 2024)
This research aims to compare human resource management (HRM) and industrial relations practices in France and Venezuela, with a focus on cultural differences, business contexts, and political, economic, and social factors. This research uses literature studies with a descriptive-qualitative type of research to analyze HR management practices and industrial relations in both countries. The sub-chapters analyzed include recruitment, selection, development, compensation, performance appraisal, and industrial relations. Human resource management practices in France tend to be less strategic, with compensation policies that change frequently and performance appraisals that do not meet expectations. On the other hand, Venezuela faces challenges in recruiting and retaining talented employees due to an unstable political, social and economic environment. Differences in industrial relations practices in the two countries reflect the unique challenges and national contexts of each country. The implication of this research is the need to focus on human resource strategies that are appropriate to the economic and regulatory conditions of each country. Differences in human resource management and industrial relations practices in France and Venezuela indicate the need to adapt human resource management and industrial relations strategies to local conditions.